Effectiveness of counseling program based on theory of rational emotive behavioral therapy in modifying irrational thoughts and reducing psychological stress among sample of mothers with down syndrome in Jordan - Esteteh, Reema Mohammad Saeed; Al-Qaisy, Lama Majed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the impact of counseling program based on the theory of rational emotive behavioral therapy to modify irrational thoughts and reducing stress in a Sample of Mothers of Children with Down Syndrome, the study sample is experimental group consisting of (15) mothers, and control group consisting of (15) mothers, stress and irrational thoughts scales were applied. The result showed statistically significant differences at the level of significance (α =0.05) between means scores of the experimental group and control group on irrational thoughts and stress scales and in favor of the experimental group. The result showed that there was no statistically significant differences at the level of significance (α =0.05) between the means scores of the experimental group of irrational thoughts and stress depending of the variable of the child gender.